Folate Receptor-Targeting and Reactive Oxygen Species-Responsive Liposomal Formulation of Methotrexate for Treatment of Rheumatoid Arthritis - Minglei Chen; Kambere Daddy Amerigos J.C; Zhigui Su; Nida El Islem Guissi; Yanyu Xiao; Li Zong; Qineng Ping (MDPI AG, 2019)
Multifunctional nanomedicines with active targeting and stimuli-responsive drug release function utilizing pathophysiological features of the disease are regarded as an effective strategy for treatment of rheumatoid arthritis (RA). Under the inflammatory environment of RA, activated macrophages revealed increased expression of folate receptor and elevated intracellular reactive oxygen species (ROS) level. In this study, we successfully conjugated folate to polyethylene glycol 100 monostearate as film-forming material and further prepared methotrexate (MTX) and catalase (CAT) co-encapsulated liposomes, herein, shortened to FOL-MTX&CAT-L, that could actively target to activated macrophages. Thereafter, elevated intracellular hydrogen peroxide, the main source of ROS, diffused into liposomes and encapsulated CAT catalyzed the decomposition of hydrogen peroxide into oxygen and water. Continuous oxygen-generation inside liposomes would eventually disorganize its structure and release the encapsulated MTX. We characterized the in vitro drug release, cellular uptake and cytotoxicity studies as well as in vivo pharmacokinetics, biodistribution, therapeutic efficacy and safety studies of FOL-MTX&CAT-L. In vitro results revealed that FOL-MTX&CAT-L possessed sufficient ROS-sensitive drug release, displayed an improved cellular uptake through folate-mediated endocytosis and exhibited a higher cytotoxic effect on activated RAW264.7 cells. Moreover, in vivo results showed prolonged blood circulation time of PEGylated liposomes, enhanced accumulation of MTX in inflamed joints of collagen-induced arthritis (CIA) mice, reinforced therapeutic efficacy and minimal toxicity toward major organs. These results imply that FOL-MTX&CAT-L may be used as an effective nanomedicine system for RA treatment.